Implementasi Model Pembelajaran Berbasis Gamifikasi untuk Meningkatkan Minat Belajar Anak Usia Dini - Nurnaningsih, Sri Maya; Malik, Lina Revilla (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to increase early childhood interest in learning at Nur Hikmah Samarinda Kindergarten through a gamification-based learning model. The background to this research is children's low interest in learning caused by less interesting learning methods. This research uses a qualitative approach with a classroom action research design carried out in two cycles. Data was collected through observation, interviews and documentation. The research results show that the application of gamification can increase children's attention, enthusiasm, active involvement and independence in learning. The discussion shows that gamification is effective in increasing learning motivation based on learning theories. In conclusion, gamification is an effective learning model for increasing early childhood interest in learning at Nur Hikmah Samarinda Kindergarten